Middle Mesozoic to Present Geological Evolution of the Central-Northern Sector of the Falkland/Malvinas Plateau as Inferred From Seismic Data - Petruccione, E. (2011)
The sequence stratigraphy is a methodology that, by means of the recognition of depositional sequences in stratigraphic architecture, reconstructs tectonic phases and relationships between tectonic, sedimentation and eustasy. A seismo-stratigraphic study of the northern sector of the Falkland Plateau (FMP) is derived from integrated analysis of two unpublished seismic reflection profiles combined with published seismic profiles, bathymetric and well data. Data analysis allowed the identification of an acoustic basement, four seismic sequences (A to D) and their bounding unconformities (r1, r2, r3 and r4), aged from middle Jurassic to Present. The precambric acoustic basement, bounded by r1 unconformity, overlain by the Middle-Late Jurassic syn-rift continental deposits of sequence A, which is bounded at the top by the r2 unconformity, testify a tectonic behaviour of uplift around the Jurassic/Cretaceous boundary. The overlying sequences B and C represent the post-rift phase. From the late Cretaceous up to Cretaceous/Paleogene boundary, a widespread erosion in the northern part of the FMP is suggested by the r4 unconformity cutting the underlying sequences C and B. The erosion is probably due to a southward tilting linked to underthrusting of the southern sector of the FMP. The lower and constant thickness of sequence D suggests, during the Cenozoic, a slow rate of subsidence, probably linked to the contemporaneous stop of the subduction of the FMP under the Scotia Plate.